(untitled) (Veterinária Notícias, 2020)
This study aimed both to evaluate the metabolic profile of lambs fed with extruded forage and concentrate containing different roughageconcentrate ratios (R:C) and to evaluate in-vitro ruminal fermentation kinetics of these rations. An experiment was carried out with 20 weanling, female crossbred lambs (½Dorper x ½Santa Inês) aged 120 ± 8 days. The treatments were four R:C ratios of extruded forage (Foragge®) and extruded concentrate (Beef Total®) – 30%F:70%C, 40%F:60%C, 50%F:50%C, and 60%F:40%C – distributed randomly with five replicates. The analysis targeted energy metabolites (VLDL, triglycerides, and cholesterol), hepatic metabolites (alkaline phosphatase, gamma glutamyltransferase [GGT], and aspartate aminotransferase [AST]), and protein metabolites (total protein, uric acid, urea, creatinine, albumin, and globulin). In-vitro gas production was quantified by inoculating the extruded rations in bovine ruminal fluid with the following forage:concentrate proportions evaluated: 30%F:70%C, 40%F:60%C, 50%F:50%C, 60%F:40%C and 70%F:30%C. Fermentation kinetic values were compared using parallelism test and curve identity at the error probability level of 5%. A regression study was used to compare the means of the metabolites at the error probability level of 5%. Average dry matter intake data are provided descriptively. The extruded ration increased the hepatic metabolites (GGT and AST) without compromising the liver and kept the energy metabolites stable. Similarly, the serum concentration of protein metabolites remained at normal levels recommended to the ovine species. In-vitro fermentation pattern displayed high gas production associated with high ration digestibility. The extruded ration provides protein and energy supply to meet the animals’ nutritional requirements without compromising their health.